Anatomical Study of the Superficial Palmar Arch, its Relation to the Kaplan Cardinal Line and Literature Review - Arroyo Berezowsky, Claudia; Gutiérrez, Alejandro Espinosa; Fresnedo, Jimena Quinzaños; Montero, José Antonio Rivas (Revista Iberoamericana de Cirugía de la Mano, 2018)
Introduction The superficial palmar arch is the main contributor to the vascular supply of the hand. Numerous anatomical variants have been described and there are multiple classifications of the superficial palmar arch available. The Kaplan cardinal line is used occasionally as a reference to identify the deep structures of the hand. However, there are also multiple variants of the line and multiple reports regarding the structures that can be identified with it.Material and Methods Ten anatomical dissections of hands were performed in seven cadaveric specimens. The anatomical variants of the superficial palmar arch were recorded, as well as their relationship with the Kaplan cardinal line. A review of the available literature was made.Results According to the classification by Coleman et al, the most common type was the complete superficial palmar arch, present in seven hands, while the incomplete superficial palmar arch was found in three hands. The most frequent complete palmar arch was type IB, followed by type IIB, and finally type IA and type IIA. The most common relation was with the Kaplan cardinal line type A to the apex of the arch and with type B to the curvature of the ulnar artery.Conclusions There is a great anatomical variability in the superficial palmar arch. There was a greater frequency of the complete superficial palmar arch, with the ulnar artery being the dominant vascular supply. The Kaplan cardinal line can be used as a safety limit to avoid the superficial palmar arch if it is drawn to intersect the pisiform bone.Clinical Relevance It is important to be aware of the anatomical variants of the superficial palmar arch, as well as of its relationship with the superficial structures of the hand to be able to perform invasive or reconstructive procedures and to preserve the vascularity of the hand.Introducción El aporte vascular de la mano está dado principalmente por el arco palmar superficial. Se han descrito numerosas variantes anatómicas del arco palmar superficial y existen múltiples clasificaciones en la literatura mundial. La línea cardinal de Kaplan es utilizada en ocasiones como referencia para identificar estructuras profundas en la mano, sin embargo, también existen múltiples variantes y discrepancia en sus relaciones con las estructuras profundas de la mano.Material y Método Se realizaron diez disecciones anatómicas en siete especímenes cadavéricos. Se identificaron las variantes anatómicas del arco palmar superficial y su relación con cuatro variantes descritas de la línea de Kaplan, se realizó una revisión de la literatura.Resultados De acuerdo a la clasificación de Coleman & Anson fue más común el arco palmar completo (7 casos) que el incompleto (3 casos). El tipo más frecuente de arco palmar superficial completo el tipo IB, seguido del tipo IIB y al final el tipo IA y el tipo IIA. La línea de Kaplan con más relación con el arco palmar fue la tipo B en la curvatura y con la línea A en el ápice. Existe discrepancia en la frecuencia del tipo de arco palmar superficial dependiendo de la clasificación utilizada.Conclusiones Existe gran variabilidad anatómica en el arco palmar superficial. Hubo una mayor frecuencia de arco palmar superficial completo y el predominio de aporte vascular fue de la arteria cubital. La línea cardinal de Kaplan puede servir como un límite de seguridad para evitar el arco palmar superficial si se traza hacia el hueso pisiforme. Importancia Clínica: Se deben conocer las variantes anatómicas del arco palmar superficial y su relación con las estructuras superficiales de la mano para realizar procedimientos quirúrgicos en la mano.
Keywords: superficial palmar arch; hand; vascularity